Analisis Peran Corporate Communication pada PT. ASDP Indonesia Ferry (Persero) - Raditya Cakra Gumilar; Roni Faslah; Suherdi Suherdi (Journal Economic Excellence Ibnu Sina, 2025)
Corporate Communication helps companies build trust and loyalty by conveying consistent and transparent messages to the public. The main objective of Corporate Communication is to build and maintain a positive image of the company and ensure that the messages conveyed are consistent and support the company's strategic objectives. Through transparent and honest communication, companies can increase the trust and loyalty of customers and other stakeholders. This study aims to analyze the role of Corporate Communication in handling the communication crisis that occurred at PT ASDP Indonesia Ferry (Persero), particularly during the traffic congestion at Merak Port during the 2024 Eid al-Fitr transportation period. This research uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, in-depth interviews with four key informants from the Corporate Communication Division, and documentation. The results of the study show that ASDP's Corporate Communication plays a leading role in conveying information, building an accurate narrative, and maintaining the company's reputation during a crisis. The main challenges faced include limited time to respond to crises (the golden hour), conflicting information on social media, and a lack of internal coordination. The strategies implemented include the rapid, decisive, empathetic, and open dissemination of information based on the principles of effective crisis communication. This study emphasizes the importance of structured and adaptive corporate communication in dealing with public pressure to build trust and maintain the institution's image.